Microalgae to biofuels evaluation through experimentally validated models - Quinn, Jason, author; Bradley, Thomas H., advisor; Marchese, Anthony J., committee member; Willson, Bryan D., committee member; Siller, Thomas J., committee member (Colorado State University. Libraries, 2011)
To view the abstract, please see the full text of the document.
Keywords: biofuels; diffuse light growth; life cycle assessment; microalgae; model; photobioreactor